International Collaborative Experiences to Design Areas Prone to Flood: Intervention in the Southern part of Resistencia (Argentina) - Valeria Schneider; María José Roibón; María Victoria Valenzuela; Julio Borges Nogueira (Department of Architecture Universitas Muhammadiyah Jakarta, 2021)
The Brian A. Thomson Institute of Urban and Regional Planning of the Faculty of Architecture and Urbanism of the UNNE (Argentina) and the Jurusan Arsitektur Fakultas Teknik, Faculty of Engineering, Universitas Muhammadiyah Jakarta (Indonesia), have been developing joint activities within approved projects since 2015, as part of a framework of International Cooperation Agreement. Faced with the global context situation due to the Covid19 pandemic, where virtual activities flourished, it was considered an opportunity to bring together teams from both institutions in a joint activity. Therefore, an